Study on the Effect of Prenatal Gentle Yoga Poses on the Level of Discomfort during the First Trimester of Pregnancy - Hamidah, Riawati; Inayah, Indun Mala; Safniah, Rohmi (Lembaga Publikasi Ilmiah Nusantara, 2025)
This study aims to examine the effect of prenatal gentle yoga poses on the level of discomfort experienced by pregnant women in the first trimester. The first trimester of pregnancy is often accompanied by physical symptoms such as nausea, dizziness, and fatigue, which can affect the quality of life of pregnant women. Gentle yoga, with a focus on calm breathing, gentle movements, and relaxation, is known to provide physical and mental benefits. The research method used is a quasi-experiment with pretest and posttest involving 30 pregnant women in the first trimester, divided into two groups: an intervention group that participated in prenatal gentle yoga sessions and a control group that did not receive the intervention. The study used a questionnaire to measure the level of physical discomfort before and after the intervention. The results show that the group that participated in prenatal gentle yoga experienced a significant reduction in discomfort compared to the control group. These findings suggest that prenatal gentle yoga poses can be an effective method for reducing discomfort in first-trimester pregnant women, as well as improving physical and mental well-being during pregnancy.